Perceptual Grouping of Random Dot Patterns in the Presence of a Tilting Frame. (April 2022) - Sarami, Arefe; Afhami, Reza; Mokhtari, Setareh
The objective of this study was to investigate the effect of tilting a frame on the perceptual organization in random dot patterns. Ten random patterns of nine dots were generated. For each pattern, a square frame was tilted at seven angles around the dots. Ten observers were asked to indicate the groups of dots in each stimulus. Each stimulus was seen 4 times by each observer which enabled us to study within-subject consistencies provided grouping reports. Within- and between-subject consistencies were computed to study if the responses provided by participants were consistent and thus reliable. The dominant group was defined as the most repeated group in all 40 reports (10 participants, 4 repetitions) obtained for each stimulus. We studied how tilting a frame affected the dominant group in each dot pattern. Perceptual grouping was not affected by tilting the frame. Based on a qualitative inspection, we remark that fundamental principles, for example, proximity, good continuation, and closure, respectively, in the order of strength, may remain the main drivers of the grouping behavior, irrespective of differences in the number of dots in each group, and the frame orientation. The numerosity condition did not affect our results. Similar trends were observed in patterns of 9 and 18 dots patterns.